Невідомі листи делегації уряду Карпатської України до уряду Угорщини - Пагіря, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The present article is dedicated to the negotiations between the governments of two states that took place in March 1939. The author made the translation of Carpathian Ukraine’s letters to the Hungarian government.